1992
DOI: 10.3109/08860229209047662
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy: Acute Renal Failure, Acute Tubular Necrosis, and Features of Postinfectious Acute Glomerulonephritis

Abstract: From 1976 to 1987 on our Nephrological Unit, 57 patients with IgA nephropathy (IgAN) proven by renal biopsies were found. Three of those presented with acute tubular necrosis (ATN) and glomerulitis, without extrarenal predisposing cause in two; and showed, as prominent manifestation, a severe acute renal failure syndrome (ARFS), needing dialytic treatment. All three had hematuria, which was macroscopic in two and microscopic in one. Thus the prevalence of the association of glomerulitis and ATN was about 5.2%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…It has been documented that I/R injury is associated with complement activation (1) and renal cell apoptosis (2). Both anaphylatoxin (C3a, C5a)-dependent and membrane attack complex-dependent mechanisms have been proposed as means by which the complement cascade induces tissue injury in animal models of renal I/R injury (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…It has been documented that I/R injury is associated with complement activation (1) and renal cell apoptosis (2). Both anaphylatoxin (C3a, C5a)-dependent and membrane attack complex-dependent mechanisms have been proposed as means by which the complement cascade induces tissue injury in animal models of renal I/R injury (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%
“…In addition, ischemic acute renal failure, conventionally referred to as acute tubular necrosis (ATN) (2), has a high mortality rate, approaching an average of 50% in some series (3). Although the pathogenesis of human ATN is complex and incompletely understood, recent studies in animals have demonstrated a pivotal role for the complement system in mediating renal IRI (4)(5)(6). There appear to be two primary complement pathways in the development of IRI, the classical pathway and the alternative pathway, both dependent on complement activation (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The kidney is unique in organ IRI and complement, since activation subsequent to IRI occurs only via the alternative pathway (12). Both anaphylatoxin (C3a, C5a)-dependent and membrane attack complex (MAC)-dependent mechanisms have been proposed as a means by which the complement cascade induces tissue injury in animal models of renal IRI (4)(5)(6)13,14). The kidney represents a major extra-hepatic site for the synthesis of the third complement component (C3), and therefore, has an important pro-inflammatory role in renal transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…PSGN or PIGN is one of the common glomerulopathies superimposed on various types of original glomerular diseases, including IgA nephropathy [3][4][5][6][7][8][9], membranous nephropathy [27], and focal segmental glomerulosclerosis [31]. In the present study, five patients (56%) had PSGN or PIGN as a superimposed glomerulopathy.…”
Section: Discussionmentioning
confidence: 91%
“…Several reports have concerned IgA nephropathy superimposed by PSGN or PIGN [3][4][5][6][7][8][9]. The incidences of IgA nephropathy and PSGN/PIGN are relatively high, but no relationship between their pathogenesis is known.…”
Section: Discussionmentioning
confidence: 97%